Learning from the Bauhaus: Imagining New Schools of Architecture (EAAE Annual Conference Proceedings, 2023)
Inspired by the study of the Bauhaus, The Architectural Association and the Glasgow School of Art, seventeen students in their final year of Architecture at Nottingham Trent University, designed their final projects with sustainability as a core foundation. This Atelier – “The New Bauhaus? Re-thinking Architecture: Sustainability is sexy” – was divided into two groups to develop the research behind their design projects. The first group revolved around ideas of building sustainably; the second one, which I led, embraced sustainability as building and supporting resilient communities, highlighting approaches that promoted sense of community and belonging, creativity, communities and connectivity.